UKIRAN MOTIF PADA MUSEUM RUMAH ADAT BAANJUANG DI KOTA BUKITTINGGI, SUMATRA BARAT - Rama Firman; Ranelis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Carving Motifs at the Baanjuang Traditional House Museum in Bukittinggi, West Sumatra The Baanjuang Traditional House Museum in Bukittinggi is a cultural heritage building that displays various traditional Minangkabau carving motifs with significant aesthetic and philosophical values. This study aims to describe the forms of carving motifs and their placement within the museum building. The research employed a qualitative descriptive method. Data were collected through field observations, interviews with museum guides, cultural experts, carving craftsmen, documentation, and literature studies. The findings reveal six principal carving motifs: Lapiah Ampek, Aka Tangah Duo Gagang, Jalo Taserak, Aka Duo Gagang, Jarek Takambang, and Sitampuak Manggih. These motifs are stylized representations of flora, fauna, and natural elements rooted in Minangkabau carving traditions. Their placement follows the structural and functional arrangement of the rumah gadang architecture, including pillars, windows, wall panels, and galuang kandang sections. Beyond their decorative role, the motifs embody symbolic meanings derived from the Minangkabau philosophy of Alam Takambang Jadi Guru. This study contributes to the documentation and preservation of traditional Minangkabau carving heritage.